2021
DOI: 10.9745/ghsp-d-21-00240
|View full text |Cite
|
Sign up to set email alerts
|

Improving Data Integrity in Public Health: A Case Study of an Outbreak Management System in Nigeria

Abstract: The design of an outbreak management system to automate and streamline data collection and validation at drive-through COVID-19 test centers ensured the fast and efficient data and sample collection and ensured that all data that were collected were accurate and complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, HCD is on the rise in public and global health, where it has been used to define community problems, design interventions, evaluate program impacts, increase the usability of health solutions, and more [29, 30,31]. In fact, numerous studies have found that HCD is particularly well-suited to address global health challenges [28,[32][33][34][35]. Teams across several regions and continents have utilized HCD to tackle diverse health-related issues, such as enhancing HIV care, addressing noncommunicable diseases, and combating violence against women [28,33,36].…”
Section: Human-centered Design Researchmentioning
confidence: 99%
“…However, HCD is on the rise in public and global health, where it has been used to define community problems, design interventions, evaluate program impacts, increase the usability of health solutions, and more [29, 30,31]. In fact, numerous studies have found that HCD is particularly well-suited to address global health challenges [28,[32][33][34][35]. Teams across several regions and continents have utilized HCD to tackle diverse health-related issues, such as enhancing HIV care, addressing noncommunicable diseases, and combating violence against women [28,33,36].…”
Section: Human-centered Design Researchmentioning
confidence: 99%
“…The Tijani et al 11 article, an example of "design as spark," demonstrates how successful co-creation approaches can lead to successful outcomes. They discuss an outbreak management system at the Nigerian Institute of Medical Research drive-through center that seeks to improve data management within the country's current health information system.…”
Section: Design As Sparkmentioning
confidence: 99%